Foraging behaviour and daily time budget of Scaly-sided Merganser Mergus squamatus breeding on Iman River, Russia. - Solovieva, D V (Wildfowl, 2013)
Daily time budget (DTB), foraging behaviour and the human affect on DTB of breeding Scaly-sided M erganser were studied on the upper Iman River, Prim orye, Russia. Daytime averaged 14.8 hours in the period from arrival on the breeding grounds until m id-incubation. The Scaly-sided M erganser is a daytime feeder, and feeding increased prior to night [F7 i36=2.34, P<0.03). Detailed DTB was obtained for entire breeding peri.